2019
DOI: 10.3390/biology8020038
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Parkinson’s Disease—Cause or Consequence?

Abstract: James Parkinson first described the motor symptoms of the disease that took his name over 200 years ago. While our knowledge of many of the changes that occur in this condition has increased, it is still unknown what causes this neurodegeneration and why it only affects some individuals with advancing age. Here we review current literature to discuss whether the mitochondrial dysfunction we have detected in Parkinson’s disease is a pathogenic cause of neuronal loss or whether it is itself a consequence of dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
171
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 196 publications
(257 reference statements)
2
171
0
2
Order By: Relevance
“…Quality control of mitochondria is crucial for the cell, because the loss of mitochondrial function is associated with various diseases, e.g. heart failure [80] or Parkinson´s disease [81]. However, in our melanoma cell model a nanoceria triggered and H 2 O 2 mediated mitochondrial dysfunction is desired to force the tumor cells to undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Quality control of mitochondria is crucial for the cell, because the loss of mitochondrial function is associated with various diseases, e.g. heart failure [80] or Parkinson´s disease [81]. However, in our melanoma cell model a nanoceria triggered and H 2 O 2 mediated mitochondrial dysfunction is desired to force the tumor cells to undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of research suggest that mitochondrial dysfunction plays a critical role in the development of both idiopathic and familial PD [4,5]. Indeed, various studies reported impairments in the respiratory chain due to environmental toxins (e.g., rotenone) that are powerful inhibitors of mitochondrial Complex I while post-mortem studies found widespread impairments in Complex I and Complex II of the respiratory chain in SNPC, hippocampus, putamen, and pedunculopontine nucleus of PD patients [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last year, genetic studies are suppling further evidence on the critical role played by mitochondria in the pathogenesis of PD [4,5]. Among the many pathogenic gene mutations, autosomal recessive Parkin and PINK1 mutations seem to be strictly linked to mitochondrial dysfunctions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor dysfunctions that characterize PD are believed to stem from on the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc), and the corresponding loss of their downstream terminals in the striatum. Dopaminergic neurons appear to be particularly vulnerable to mitochondrial damage and autophagy dysfunction (Chen et al, 2019;Sato et al, 2018). While mitochondrial dysregulation is associated with oxidative stress and diminished energetic supply to the cell, the inhibition of autophagy observed affects the ability of the cell to manage misfolded proteins that are characteristic of PD pathology.…”
Section: Parkinson's Diseasementioning
confidence: 99%